2019
DOI: 10.3389/fmech.2019.00016
|View full text |Cite
|
Sign up to set email alerts
|

An Overview: Laser-Based Additive Manufacturing for High Temperature Tribology

Abstract: Laser-based additive manufacturing (LBAM) is a versatile manufacturing technique, extensively adopted to fabricate metallic components of enhanced properties. The current review paper provides a critical assessment of the fabricated metallic coatings and parts through LBAM-processes [e.g., laser metal deposition (LMD) and selective laser melting (SLM)] for high temperature tribological applications. A succinct comparison of LBAM-fabrication and conventional manufacturing is given. The review provides an insigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 136 publications
(138 reference statements)
0
10
0
Order By: Relevance
“…The conducted studies have shown that efficient operational performance as the target yields the best results as the tool, die, or mold is designed for and made by L-PBF [1,11,25,[30][31][32][33][34][35][36]. This review shows that it is possible to improve this operational performance by adding LMPp (DED-p, LC) for surface functionalization [41][42][43][44][45][46][47][48][49][50][51] and tool, die, or mold remanufacture [52,[56][57][58][59][60][61][62][63][64]. Tool remanufacture can, in other words, be added as a factor that influences the tool life and thereby the operational efficiency during the tool life cycle.…”
Section: Discussion and Outlookmentioning
confidence: 99%
See 2 more Smart Citations
“…The conducted studies have shown that efficient operational performance as the target yields the best results as the tool, die, or mold is designed for and made by L-PBF [1,11,25,[30][31][32][33][34][35][36]. This review shows that it is possible to improve this operational performance by adding LMPp (DED-p, LC) for surface functionalization [41][42][43][44][45][46][47][48][49][50][51] and tool, die, or mold remanufacture [52,[56][57][58][59][60][61][62][63][64]. Tool remanufacture can, in other words, be added as a factor that influences the tool life and thereby the operational efficiency during the tool life cycle.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…nickel (Ni) based hard facing alloys (NiSiB, NiCrSiB, Inconel 625 (NiCrSiBFeC) etc.) to accomplish high toughness and thermal and corrosion resistance [42,43]. iron (Fe) based alloys (316 stainless steel, Fe-Cr-Si-B alloy, Crucible Particle Metallurgy (CPM) steel) for enhanced abrasive wear and corrosion resistance (and reduction of the tool costs) [42][43][44][45].…”
Section: Tool and Die Surface Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Their use continues to extend to many industrial sector applications for components that operate in extreme conditions. LBAM technologies are unique and versatile in the manufacturing of parts with complex geometry, functionally graded or customised, producing an improvement in properties that can be used for a variety of industrial applications, such as within the aerospace, metallurgy, energy, and automotive industries [1,2]. Direct laser deposition (DLD) is an LBAM technology used for the additive manufacturing of metal parts, reconstructions, and repairs.…”
Section: Introductionmentioning
confidence: 99%
“…In these systems, various moving components, such as rolling/sliding bearings and gears, operate under extreme conditions, such as high temperatures above 400 °C, high-speed/load, corrosive, and vacuum environments [3][4][5][6]. Under such cases, traditional liquid lubricants cannot provide the desired performance because of evaporation, decomposition, coking, and sealing, among other factors [7,8]. Instead, highperformance solid-lubricating materials show great potential to fulfill the requirements of reducing friction and wear resistance of the moving parts in these harsh environments [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%